ANALYSIS TEACHERS NEEDS PRODUCTIVE AREAS OF EXPERTISE ENGINEERING BUILDING IN PADANG - 653-660 , Yocky Syaida Adha Putra (Universitas Negeri Padang, 2015)
ABSTRACT This study aims to reveal how productive the teacher needs building engineering expertise in the academic year 2014/2015 and 2024/2025 were ideal in the analysis. This research is quantitative. The unit of analysis of this study is SMK in Padang, the number of research subjects, that is SMKN 1 Padang, SMKN 1 Sumbar, SMKN 5 Padang and SMK Dhuafa Nusantara. The collection of data on research conducted by engineering documentation. Results the analysis of the needs productive teacher expertise in building engineering SMK Padang in Academic Year 2014/2015 acquired needs, which SMKN 1 Padang the total of 6 people, SMKN 5 Padang the total of 2 people, At SMKN 1 Sumbar the total of 9 people and SMK Dhuafa Nusantara the total of 8 people. Analysis the needs of the teacher productive earned Academic Year 2024/2025 acquired additional needs, which SMKN 1 Padang the total of 36 people, SMKN 5 Padang the total of 47 people, SMKN 1 Sumbar the total of 26 people and SMK Dhuafa Nusantara the total of 29 people. Keywords : Teacher Analysis, Teacher Productive, Teacher Needs